IMPLEMENTASI PERJANJIAN KREDIT PEMILIKAN RUMAH (KPR) PADA PT. BANK TABUNGAN NEGARA CABANG PONTIANAK - Dina Fitriani Wulandari; Jufianty Trisna Putri (Judge : Jurnal Hukum, 2025)
The Mortgage Agreement (KPR) of BTN PLATINUM is a home-ownership credit facility from Bank BTN designed to facilitate home purchases from developers and non-developers, either for new or second-hand houses, ready stock or under construction, as well as take-over from other banks. This study aims to examine the implementation process of mortgage agreements secured with collateral, the legal consequences of debtor default, and the dispute resolution mechanisms available when non-performing loans occur. The normative juridical method with descriptive analysis was applied to analyze legal norms and their application in practice. The findings reveal that the implementation of mortgage agreements begins with a strict selection process based on the principle of prudence, embodied in the 5C analysis (character, capacity, capital, collateral, condition of economy). Once approved, the bank issues the SP3K (Confirmation of Credit Provision) which formalizes the agreement and binds the collateral. Debtors who default are subject to sanctions ranging from fines to foreclosure of collateral, while BTN provides opportunities for restructuring, rescheduling, and settlement to minimize disputes. The study underscores the importance of ensuring legal certainty and balancing the rights and obligations of both creditors and debtors in order to maintain financial stability and public trust in the banking system.